PERAWATAN PREVENTIF MESIN BUBUT MENGGUNAKAN METODE ANALISIS GETARAN DALAM BERBAGAI KONDISI KECEPATAN SPINDLE - Soemardi, Heryanto Budiono (Otopro, 2020)
This research proposes a new idea of the preventive maintenance method of the lathe by analyzing the vibration on the fixed gear gearbox of the Maximat lathe. From the results of the vibrations that occur, checks are carried out on the lubricating oil, disability of the existing gears and bearings, and then repairing the gear and bearing and replacing the lubricating oil. To find out the magnitude of vibration that occurs in this maximat lathe, rotation variations are carried out by 1000 (rpm), 1500 (rpm) and 2000 (rpm). The highest average amplitude value at 1000 RPM engine speed is on the Bu04 machine with a value of 0.034 mm / s RMS while the lowest value is obtained on the Bu03 lathe with a value of 0.029 mm / s RMS. At 1500 RPM engine speed, the highest average amplitude value is obtained on the Bu03 lathe with a value of 0.045 mm / s RMS. On the Bu02 lathe with a value of 0.032 mm / s RMS. At 2000 RPM engine speed, the highest average value of amplitude was obtained in the Bu03 lathe with a value of 0.069 mm / s RMS. While the lowest value obtained on the Bu02 lathe with a value of 0.050 mm / s RMS. The lower the vibration of the lathe, the more optimal the results of turning. There is an influence between the speed of the engine against the vibrations that occur. Lathe with a high amplitude level indicates that there are components that need attention